The Ankle-brachial Index as a Predictor of Multivess el Coronary Disease in Patients with Acute Coronary Syndrome and Peripheral Arterial Disease - Tessa Negrín Valdés; Ailed Elena Rodríguez Jiménez; Raikel Fardales Rodríguez; Luis Alberto Castellanos Gallo; José Carlos Meneses Jiménez; Magda Alina López Callejas (Revista Finlay)
Background: the coexistence of peripheral arterial disease and acute coronary syndrome is associated with a worse prognosis. The ankle-brachial index has been shown to be a marker of multisite atherosclerosis. Objective: to determine the relationship between the ankle-brachial index and coronary artery disease. Method: an analytical observational study was carried out that included all the patients discharged from the coronary care unit of the Camilo Cienfuegos Gorriarán Provincial University Hospital, of the Sancti Spíritus province, in the period from March 1, 2011 to February 30 of 2018, with a diagnosis of acute coronary syndrome, with and without ST segment elevation. Clinical data, ankle-brachial index, echocardiography and coronary angiography were collected and the prognostic implication of the index in disease was determined through a classification tree with the variables included in the binary logistic regression model. Results: multivessel disease occurred in 85.2 % patients, 81.9 % of them were men, 85.9 % of them with multivessel disease, the mean age was 59.1 years, 52.3 % presented STEACS with multivessel disease 78.8 %. The most frequent risk factors were: smoking (86.8 %), dyslipidemia (85.8 %) and arterial hypertension (84.8 %) in the group with multivessel disease and ABI = 0.9 (SD = 0.3). They received treatment with clopidogrel (86.1 %), acetylsalicylic acid (86.3 %), ACEI or ARB (85.8 %), statins (73.2 %), beta-blockers (87.5 %) and nitrates (86, 3 %). On angiography, 85.2 % had severe coronary disease. The two-predictor variables were: NSTEACS and ABI≤0.9, which showed a high positive predictive value in the prognosis of multivessel coronary artery disease. Conclusions: ankle-brachial index <0.9 showed a predictive capacity for multivessel disease that increases if it is associated with diabetes mellitus and smoking.